Discrimination of beef production system and regional geography by multivariate analysis of stable isotope ratios (C, N, S, O, H) - Hannah Whyte; Raquel Cama-Moncunill; Peter G. Dunne; Aidan P. Moloney; Frank McDermott; Matta Ebaid; Michael Salter-Townshend; Frank J. Monahan; Olaf Schmidt (Food Control, 2026)

Changes in Body Size With Age Do Not Follow the Temperature‐Size Rule - Jennifer S. Bigman; Lewis A. K. Barnett; James T. Thorson; Sean C. Anderson; Krista B. Oke; Kelly A. Kearney; Darren J. Pilcher; Wei Cheng; Esther D. Goldstein; Mary E. Matta; Kirstin K. Holsman; Lauren A. Rogers (Global Ecology and Biogeography, 2026)
Aim The temperature‐size rule is often described as a reduction in ectothermic asymptotic or maximum body size with warming. Although this coincides with the expectation that faster growth under warming would lead to larger sizes early in life but smaller sizes later in life, there remain few tests of changes in size across ontogeny. Here, we use > 99,000 observations of weight‐at‐age of commercially important fishes over 25 years to ask whether changes in size across ontogeny can be explained by temperature. We also examine whether oxygen, a key part of a proposed mechanism behind the temperature‐size rule, explains patterns of weight‐at‐age better than temperature. Understanding how temperature and oxygen affect size across age offers a test of macroecological theory and can inform the future productivity of fisheries. Location Bering Sea, largest subarctic system (Latitude: 52° N–66° N, Longitude: 160° E–170° W). Time Period 1987–2023. Major Taxa Studied Commercially important fishes. Methods We coupled fisheries‐independent survey data and climate model output with spatiotemporal generalised linear mixed‐effects models, a novel framework for testing the temperature‐size rule. These models account for uneven sampling across space and time to assess long‐term trends, as well as the effects of temperature and oxygen on size across age. We additionally explore the effect of model structure on our results by comparing functional forms and how spatial and/or spatiotemporal random effects are included. Results Weight‐at‐age was variable over time for all species with no long‐term trend. Temperature better explained this variability than oxygen, but effects were small and not age‐specific, counter to the temperature‐size rule. Our results were sensitive to model structure as models with shared spatial effects across ages appeared to support temperature‐size rule predictions, but this support reflected spatial autocorrelation in size rather than age‐specific temperature responses. Collectively, this work shows that support for the temperature‐size rule in these fishes was an artifact of spatial patterns in size and growth. Main Conclusions Our work tests macroecological theory using nearly complete body size trajectories to understand not only changes in adult stages but how size changes across age. We highlight that relationships among size, growth, temperature, and oxygen are not as straightforward as theory suggests and illustrate that modelling decisions can have a large effect on tests of ecological theory, and more broadly, our ability to understand biological responses to climate change.

From wells to waves: Evaluating fecal contamination sources using FIB and MST markers along Texas coastal waters - Dipti Anik Dhar; Kiran Kumar Vadde; Roya Narimani; Dorina Murgulet; J. David Felix; Akanksha Matta; Jason Pinchback; Lucy Flores; Vikram Kapoor (Marine Pollution Bulletin, 2026)

Occurrence of fecal indicator bacteria and microbial source tracking markers along the Texas Gulf Coast adjoining two barrier islands - Dipti Anik Dhar; Kiran Kumar Vadde; Roya Narimani; Dorina Murgulet; J. David Felix; Akanksha Matta; Jason Pinchback; Vikram Kapoor (Science of The Total Environment, 2025)

Petrological, geochemical and geodynamic evolution of the Wadi Al-Baroud granitoids, north Arabian-Nubian shield, Egypt - Bassam A. Abuamarah; Hassan Alzahrani; Marian J. Matta; Mokhles K. Azer; Paul D. Asimow; Mahmoud H. Darwish (Journal of African Earth Sciences, 2023)

A comprehensive review of the role of microorganisms on texture change, flavor and biogenic amines formation in fermented meat with their action mechanisms and safety - Tolulope J. Ashaolu; Ibrahim Khalifa; Matta A. Mesak; Jose M. Lorenzo; Mohamed A. Farag (Critical Reviews in Food Science and Nutrition, 2023)

In Vitro Testing of Sunscreens for Dermal Absorption: Method Comparison and Rank Order Correlation with In Vivo Absorption - Yang Yang; Ann-Marie Ako-Adounvo; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Murali K. Matta; David Strauss; Theresa M. Michele; Jian Wang; Patrick J. Faustino; Thomas O’Connor; Muhammad Ashraf (AAPS PharmSciTech, 2022)

Association studies and QTL mapping for soybean oil content and composition - Luiz Cláudio Costa Silva; Loreta Buuda da Matta; Guilherme Ramos Pereira; Rafael Delmond Bueno; Newton Deniz Piovesan; Andrea J. Cardinal; Pedro Ivo Vieira Good God; Cleberson Ribeiro; Maximiller Dal-Bianco (Euphytica, 2021)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Characterization of a new GmFAD3A allele in Brazilian CS303TNKCA soybean cultivar - Luiz Claudio Costa Silva; Rafael Delmond Bueno; Loreta Buuda da Matta; Pedro Henrique Scarpelli Pereira; Danyelle Barbosa Mayrink; Newton Deniz Piovesan; Carlos Sigueyuki Sediyama; Elizabeth Pacheco Batista Fontes; Andrea J. Cardinal; Maximiller Dal-Bianco (Theoretical and Applied Genetics, 2018)

Biofiltration vs conventional activated sludge plants: what about priority and emerging pollutants removal? - R. Mailler; J. Gasperi; V. Rocher; S. Gilbert-Pawlik; D. Geara-Matta; R. Moilleron; G. Chebbo (Environmental Science and Pollution Research, 2014)

Phylogenetic analysis of canine parvovirus partial VP2 gene in India - H. K. Mukhopadhyay; Samyukta Lakshmi Matta; S. Amsaveni; P. X. Antony; J. Thanislass; R. M. Pillai (Virus Genes, 2014)

Effect of Low-Temperature Storage on Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) - R J Silva; F J Cividanes; E C Pedroso; J C Barbosa; D H Matta; E T Correia; A K Otuka (Neotropical Entomology, 2013)

Genotype-dependent effects of adolescent nicotine exposure on dopamine functional dynamics in the nucleus accumbens shell in male and female mice: a potential mechanism underlying the gateway effect of nicotine - Price E. Dickson; Tiffany D. Rogers; Deranda B. Lester; Mellessa M. Miller; Shannon G. Matta; Elissa J. Chesler; Dan Goldowitz; Charles D. Blaha; Guy Mittleman (Psychopharmacology, 2011)

Combined exposure to nicotine and ethanol throughout full gestation results in enhanced acquisition of nicotine self-administration in young adult rat offspring - Shannon G. Matta; Andrea J. Elberger (Psychopharmacology, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Prenatal alcohol exposure (PAE) reduces the size of the forepaw representation in forepaw barrel subfield (FBS) cortex in neonatal rats: relationship between periphery and central representation - Cecilia P. Margret; Tyson D. Chappell; Cheng X. Li; Taha A. Jan; Shannon G. Matta; Andrea J. Elberger; Robert S. Waters (Experimental Brain Research, 2006)

Prenatal alcohol exposure delays the development of the cortical barrel field in neonatal rats - Cecilia P. Margret; Cheng X. Li; Tyson D. Chappell; Andrea J. Elberger; Shannon G. Matta; Robert S. Waters (Experimental Brain Research, 2006)

Associations between metals and the blue mesogleal protein of Cassiopea xamachana - M. A. Phelan; J. L. Matta; Y. M. Reyes; R. Fernando; R. A. Boykins; R. S. Blanquet (Marine Biology, 2006)

Prenatal alcohol exposure alters the size, but not the pattern, of the whisker representation in neonatal rat barrel cortex - Cecilia P. Margret; Cheng X. Li; Andrea J. Elberger; Shannon G. Matta; Tyson D. Chappell; Robert S. Waters (Experimental Brain Research, 2005)

Heavy metals, lipid peroxidation, and ciguatera toxicity in the liver of the caribbean barracuda (Sphyraena barracuda) - J. Matta; M. Milad; R. Manger; T. Tosteson (Biological Trace Element Research, 1999)

Binding of synthetic sulfated ligands by human splenic galectin 1, a β-galactoside-binding lectin - Howard J Allen; Hafiz Ahmed; Khushi L Matta (Glycoconjugate Journal, 1998)

Specific activity of ?-l-fucosidase in sera with phenotypes of either low, intermediate, or high total enzyme activity and in a fucosidosis serum - Richard A. DiCioccio; Joseph J. Barlow; Khushi L. Matta (Biochemical Genetics, 1986)